Exploring the Depths of Trauma, Psychology, and Literature: Unveiling Hidden Realities in the Human Psyche and Literary Expression - Majid, Waseem (International Journal of Psychosocial Rehabilitation, 2019)
This research paper delves into the intricate interplay between trauma, psychology, and literature, aiming to uncover the concealed dimensions of the human psyche and their reflection in literary works. Drawing inspiration from Adrienne Rich’s concept of "Theory" as a tool for pattern recognition and Sigmund Freud’s foundational contributions to trauma theory, this study investigates how trauma shapes individuals’ internal landscapes and finds expression in the creative realm. Through an exploration of Freud’s theories on dreams, Oedipus and Electra complexes, and the unconscious, the paper reveals the profound influence of psychoanalysis on the depiction of human nature by novelists, critics, and poets throughout the 20th century. The paper proposes that the artistic process stems from the unconscious mind of the creator, manifesting as stories, dreams, and myths that undergo stylized transformation to convey symbolic expression. It contends that literature serves as a medium for cleansing and refining the soul and conscience, tapping into collective unconscious patterns that resonate with shared human experiences. This reciprocal relationship between psychology and literature is underscored, showcasing how psychological exploration can be akin to literary analysis and how literary psychoanalysis provides insight into the intricacies of the human psyche. In conclusion, this research offers a comprehensive view of the intricate connections between trauma, psychology, and literature. It illuminates how psychological concepts have shaped literary narratives and how literature serves as a mirror reflecting the depths of the human mind. Through the lens of various literary and psychological theories, this paper contributes to a deeper understanding of how the exploration of trauma and psychology enriches the tapestry of literary expression.